Inteligencia emocional y su incidencia en el rendimiento académico de un estudiante de bachillerato de la Unidad Educativa Caracol - Erazo Miranda, Cesar Estalyn (2020)
Through this case study, it was investigated about emotional intelligence and its incidence in the academic performance of a student of the Caracol Educational Unit, in the development it was evidenced that, indeed, the student is affected since he does not have self-control of their emotions, their greatest impact is in the educational context. This is because emotional intelligence plays an important role in the achievements or failures of people, therefore, therefore, To detect the incidence of my independent variable in the academic performance of this adolescent, I proceeded to collect information through interviews, psychotherapeutic techniques and psychometric tests, which validated my study. Based on the information collected, I established a therapeutic plan, focused on cognitive behavioral therapy, in order to restructure the thinking patterns, which are negatively reflected in the student's emotions and behavior. At the end of the process, the techniques achieved a great advance in relation to the thoughts that the adolescent initially manifested.